Gold-catalyzed direct alkynylation of tryptophan in peptides using TIPS-EBX - Tolnai, Gergely L.; Brand, Jonathan P.; Waser, Jerome (Beilstein Journal of Organic Chemistry, 2016)
The selective functionalization of peptides containing only natural amino acids is important for the modification of biomolecules. In particular, the installation of an alkyne as a useful handle for bioconjugation is highly attractive, but the use of a carbon linker is usually required. Herein, we report the gold-catalyzed direct alkynylation of tryptophan in peptides using the hypervalent iodine reagent TIPS-EBX (1-[(triisopropylsilyl)ethynyl]-1,2-benziodoxol-3(1H)-one). The reaction proceeded in 50–78% yield under mild conditions and could be applied to peptides containing other nucleophilic and aromatic amino acids, such as serine, phenylalanine or tyrosine.
Keywords: alkynes; C–H functionalization; gold catalysis; hypervalent iodine; peptides

Acetylene Chemistry: Chemistry, Biology and Material Science - Diederich, F.; Stang, P. J.; Tykwinski, R. R. (Wiley-VCH, 2005)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Lutz, J.-F. (Angew. Chem., Int. Ed., 2007)

(untitled) - Meldal, M.; Tornøe, C. W. (Chem. Rev., 2008)

(untitled) - McKay, C. S.; Finn, M. G. (Chem. Biol., 2014)

(untitled) - Stephanopoulos, N.; Francis, M. B. (Nat. Chem. Biol., 2011)

(untitled) - Takaoka, Y.; Ojida, A.; Hamachi, I. (Angew. Chem., Int. Ed., 2013)

(untitled) - Patterson, D. M.; Nazarova, L. A.; Prescher, J. A. (ACS Chem. Biol., 2014)

(untitled) - Yang, M.; Li, J.; Chen, P. R. (Chem. Soc. Rev., 2014)

(untitled) - Boutureira, O.; Bernardes, G. J. L. (Chem. Rev., 2015)

(untitled) - Koniev, O.; Wagner, A. (Chem. Soc. Rev., 2015)

(untitled) - Chalker, J. M.; Bernardes, G. J. L.; Davis, B. G. (Acc. Chem. Res., 2011)

(untitled) - Kundu, R.; Ball, Z. T. (Chem. Commun., 2013)

(untitled) - Toda, N.; Asano, S.; Barbas, C. F., III (Angew. Chem., Int. Ed., 2013)

(untitled) - Abbas, A.; Xing, B.; Loh, T.-P. (Angew. Chem., Int. Ed., 2014)

(untitled) - Obermeyer, A. C.; Jarman, J. B.; Francis, M. B. (J. Am. Chem. Soc., 2014)

(untitled) - Vinogradova, E. V.; Zhang, C.; Spokoyny, A. M.; Pentelute, B. L.; Buchwald, S. L. (Nature, 2015)

(untitled) - Joshi, N. S.; Whitaker, L. R.; Francis, M. B. (J. Am. Chem. Soc., 2004)

(untitled) - Tilley, S. D.; Francis, M. B. (J. Am. Chem. Soc., 2006)

(untitled) - Ban, H.; Gavrilyuk, J.; Barbas, C. F., III (J. Am. Chem. Soc., 2010)

(untitled) - Antos, J. M.; Francis, M. B. (J. Am. Chem. Soc., 2004)

(untitled) - Antos, J. M.; McFarland, J. M.; Iavarone, A. T.; Francis, M. B. (J. Am. Chem. Soc., 2009)

(untitled) - Popp, B. V.; Ball, Z. T. (J. Am. Chem. Soc., 2010)

(untitled) - Ruiz-Rodríguez, J.; Albericio, F.; Lavilla, R. (Chem. – Eur. J., 2010)

(untitled) - Preciado, S.; Mendive-Tapia, L.; Albericio, F.; Lavilla, R. (J. Org. Chem., 2013)

(untitled) - Mendive-Tapia, L.; Preciado, S.; Garcia, J.; Ramon, R.; Kielland, N.; Albericio, F.; Lavilla, R. (Nat. Commun., 2015)

(untitled) - Williams, T. J.; Reay, A. J.; Whitwood, A. C.; Fairlamb, I. J. S. (Chem. Commun., 2014)

(untitled) - Reay, A. J.; Williams, T. J.; Fairlamb, I. J. S. (Org. Biomol. Chem., 2015)

(untitled) - Zhu, Y.; Bauer, M.; Ackermann, L. (Chem. – Eur. J., 2015)

(untitled) - Perekalin, D. S.; Novikov, V. V.; Pavlov, A. A.; Ivanov, I. A.; Anisimova, N. Yu.; Kopylov, A. N.; Volkov, D. S.; Seregina, I. F.; Bolshov, M. A.; Kudinov, A. R. (Chem. – Eur. J., 2015)

(untitled) - Siti, W.; Khan, A. K.; de Hoog, H.-P. M.; Liedberg, B.; Nallani, M. (Org. Biomol. Chem., 2015)

(untitled) - Kodama, K.; Fukuzawa, S.; Nakayama, H.; Sakamoto, K.; Kigawa, T.; Yabuki, T.; Matsuda, N.; Shirouzu, M.; Takio, K.; Yokoyama, S.; Tachibana, K. (ChemBioChem, 2007)

(untitled) - Li, N.; Lim, R. K. V.; Edwardraja, S.; Lin, Q. (J. Am. Chem. Soc., 2011)

(untitled) - Frei, R.; Waser, J. (J. Am. Chem. Soc., 2013)

(untitled) - Frei, R.; Wodrich, M. D.; Hari, D. P.; Borin, P.-A.; Chauvier, C.; Waser, J. (J. Am. Chem. Soc., 2014)

(untitled) - Abegg, D.; Frei, R.; Cerato, L.; Prasad Hari, D.; Wang, C.; Waser, J.; Adibekian, A. (Angew. Chem., Int. Ed., 2015)

(untitled) - Brand, J. P.; Charpentier, J.; Waser, J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Tolnai, G. L.; Ganss, S.; Brand, J. P.; Waser, J. (Org. Lett., 2013)

(untitled) - Hansen, M. B.; Hubálek, F.; Skrydstrup, T.; Hoeg-Jensen, T. (Chem. – Eur. J., 2016)